The effects of the Regional Comprehensive Economic Partnership on China’s trade, tariff revenue and welfare - Zhang, Wenjie; Abd Rahman, Muhammad Daaniyall; Muhamad Senan, Mohamad Khair Afham (Sciendo, 2024)
Increasing attention is being paid to the role of regional economic integration in facilitating a country's trade. This is especially true for the state like China, which has the second largest GDP in the world. This study explores the effects of the Regional Comprehensive Economic Partnership (RCEP) on China, looking at changes in welfare, trade creation, trade diversion, and tariff revenue under four tariff reduction scenarios with RCEP members. The study evaluates how RCEP affects China's trade relations with Japan, Korea, ASEAN, Australia, and New Zealand by using the World Bank's World Integrated Trade Solution Software for Market Analysis and Restrictions on Trade (WITS-SMART) tool. The findings demonstrate increased market accessibility and competitiveness of commodities in the Chinese market, with notable increases in trade creation and diversion, especially with Korea and Japan. RCEP considerably increases welfare even though it results in lower tariff revenues, indicating that the advantages of lower trade costs and more effective supply chains exceed the fiscal drawbacks. The paper concludes with policy recommendations that emphasize the need for strategic adaptations in China’s trade policies to fully capitalize on the economic opportunities presented by RCEP, ensuring sustainable growth and the equitable distribution of trade benefits among all member states.